2021
DOI: 10.3390/jcm10040692
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Threat from COVID-19: A Cross-Sectional Study in the Spanish Population

Abstract: One of the first measures for fighting the worldwide spread of the COVID-19 pandemic is social isolation or quarantine. The perceived threat from COVID-19 in this situation, maintained over time, generates uncertainty and fears, etc., which could lead to mental disorders in the population. This study evaluated the perceived threat from COVID-19 in the Spanish population. The study design was cross-sectional and observational. The sample of 1014 participants recruited in Spain had a mean age of 40.87 (SD = 12.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…The group sharing conspiracy theories ranked third in terms of presence. This evidence supports the thesis that there are situations in which misinformation can lead to the development of conspiratorial thoughts and ideas [17,21,49]. Furthermore, it is so important to understand that antivaccination users offer a wide range of potentially attractive narratives that blend topics such as safety concerns, conspiracy theories, and the cause and cure of COVID-19, amongst others [35,36,46,47].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The group sharing conspiracy theories ranked third in terms of presence. This evidence supports the thesis that there are situations in which misinformation can lead to the development of conspiratorial thoughts and ideas [17,21,49]. Furthermore, it is so important to understand that antivaccination users offer a wide range of potentially attractive narratives that blend topics such as safety concerns, conspiracy theories, and the cause and cure of COVID-19, amongst others [35,36,46,47].…”
Section: Discussionsupporting
confidence: 66%
“…This is why these kinds of messages can be considered a public health threat [20]. In addition, we have to take into account so-called health anxiety disorder, as it is linked to a great amount of incorrect and ambiguous information to which people have access to [21,22]. This can generate abnormal behaviors both at individual and social levels, due to the loss of trust in health authorities, the blaming of people who belong to different ethnic, social, or political groups, and the development of conspiratorial thoughts [23].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we found increased levels of distress in caregivers when compared to non-caregiving population, which is consistent with previous studies [ 40 , 43 , 44 , 45 , 46 ]. Along with prior evidence, our findings also showed that higher levels of fear and PTSS symptomatology were associated with caregiving [ 17 , 39 , 40 , 41 , 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…Fear is also associated with lower self-efficacy and insecure attachment, especially in the use of avoidance behaviors to manage anxiety and as preventive strategies [ 37 , 38 ]. Besides these factors, previous evidence also suggests a relationship between high levels of fear, the perceived risk for loved ones, and concerns about infecting family members, especially in those who have a caregiving role [ 17 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, local services, having foreknowledge, could react locally, without the need to restrict large areas, which is of great importance for an economy heavily affected by the pandemic. They can designate the zones of the greatest threats, where the most intense actions should be taken, including, for example, imposing restrictions on social life, and as a result, reducing the impact on human health [48,49]. The knowledge about the structure of the system could allow making decisions appropriate to the situation, i.e., introducing restrictions only in a specific area.…”
Section: Discussionmentioning
confidence: 99%